Extracellular Matrix From Decellularized Wharton’s Jelly Improves the Behavior of Cells From Degenerated Intervertebral Disc - Penolazzi, Letizia; Pozzobon, Michela; Bergamin, Leticia Scussel; D’Agostino, Stefania; Francescato, Riccardo; Bonaccorsi, Gloria; De Bonis, Pasquale; Cavallo, Michele; Lambertini, Elisabetta; Piva, Roberta (Frontiers in Bioengineering and Biotechnology, 2020)
Regenerative therapies for intervertebral disc (IVD) injuries are currently a major challenge that is addressed in different ways by scientists working in this field. Extracellular matrix (ECM) deriving from decellularized non-autologous tissues has been established as a biomaterial with remarkable regenerative capacity and its potential as a therapeutic agent is rising. In the present study, we investigated the potential of decellularized Wharton’s jelly (DWJM) from human umbilical cord to act as an ECM-based scaffold for IVD cell culturing. An efficient detergent-enzymatic treatment (DET) was used to produce DWJM maintaining its native microarchitecture. Afterwards, immunofluorescence, biochemical assays and electron microscopy analysis showed that DWJM was able to produce sizeable 3D cell aggregates, when combined with human mesenchymal stromal cells isolated from WJ (MSCs) and IVD cells. These latter cells are characterized by the loss of their chondrocyte-like phenotype since they have been isolated from degenerated IVD and in vitro expanded to further de-differentiate. While the effect exerted by DWJM on MSCs was essentially the induction of proliferation, conversely, on IVD cells the DWJM promoted cell differentiation towards a discogenic phenotype. Notably, for the first time, the ability of DWJM to improve the degenerated phenotype of human IVD cells was demonstrated, showing that the mere presence of the matrix maintained the viability of the cells, and positively affected the expression of critical regulators of IVD homeostasis, such as SOX2, SOX9 and TRPS1 transcription factors at specific culture time. Our data are in line with the hypothesis that the strengthening of cell properties in terms of viability and expression of specific proteins at precise times can guide recovery of cellular functionality and trigger regenerative potential. Currently, there are no definitive surgical or pharmacological treatments for IVD degeneration (IDD) able to restore the disc structure and function. Therefore, the potential of DWJM to revert degenerated IVD cells could be exploited in the next future an ECM-based intradiscal injectable therapeutic.